Diseño de una solución DCIM, basada en herramientas open source para un centro de datos experimental - Carrión Bravo, Miguel Ángel (2019)
The purpose of this document is the design of a DCIM (Data Center Infrastructure Administration) solution, which is based on the use of open source tools that allow its sketch within the University's experimental data center. For the fulfillment of this work, four stages have been structured, which are shaped as follows. The first phase corresponds to the investigation and compilation of all the information that forms the basis for the structuring of the project. Next, you have the analysis of all the information collected. To establish comparisons between commercial use systems, with solutions available in the market which are developed in open source. In addition, it has the respective analysis of the situation of the experimental data center of the University, before choosing the tool for its study. Completed with the analysis of all the existing solutions and chosen the tool for its use, the design of the solution to be applied is elaborated. Here it will be schematized in a virtual environment. In which, with the collection of previous data, all this information is fed to the system. Finally, as a result of the results obtained in the design and testing of the system, the conclusions and recommendations corresponding to the use of the tool will be obtained.